Persistence of pathogens and biocontrol potential in the bell pepper fruit mycobiome from flowering to postharvest - Karoney, Edwin M.; Gokul, Jarishma K.; Siyoum, Nazareth; Molelekoa, Tintswalo; Korsten, Lise (Frontiers in Horticulture, 2025)
IntroductionSeveral postharvest strategies have been explored to prevent postharvest losses of fruit and vegetables in small-scale production environments that are caused by fungal spoilage during storage; however, the losses remain persistent. In the bell pepper industry for instance, approximately 40% of the total global production is lost annually, highlighting a need to understand pathogen dynamics at the preharvest stage that could contribute to tissue breakdown at storage. This study therefore aimed to explore fungal community shifts during bell pepper fruit development from flowering to storage.MethodsThe samples of flowers, small fruits, mature fruits at harvest and storage were processed to identify the fungal composition using next-generation sequencing of the internal transcribed spacer region.ResultsThe results showed that bell pepper harbored 346 fungal genera across all fruit stages mainly from the phyla Ascomycota (83.9%) and Basidiomycota (15.3%). The fungal community comprised both pathogenic and beneficial taxa: Cladosporium, Alternaria, and Fusarium were among the most abundant probable pathogenic taxa, while Aureobasidium, Filobasidium, and Sampaiozyma represented potential biocontrol agents (BCAs). Trend and correlation analysis showed an antagonistic relationship between the BCAs and pathogenic fungi, possibly explaining their dynamic composition across the fruit stages.DiscussionThe analysis showed interaction likelihood between pathogenic taxa, giving insights into co-infection, as well as among beneficial taxa with biocontrol potential, highlighting their synergistic effect against pathogens. Based on redundancy analysis, fruit physiological changes across the developmental stages may have accounted for approximately 8.53% of the total microbial variation observed and could favor growth of spoilage pathogens at storage. The overall analysis confirmed that primary infection at the early fruit developmental stage was the source of the bell pepper decay at postharvest. This highlights the critical need to refocus postharvest spoilage management on reducing preharvest infection, particularly those relating to quiescent infections. The antagonistic characteristics in the bell pepper mycobiome can be harnessed for the development of biocontrol consortia targeting dual/multiple infections. These findings offer a new approach to the management of postharvest losses while aligning with sustainable agricultural production and food security by promoting the use of naturally occurring beneficial microbes for crop protection.